Larval chaetotaxy and morphometry of Megasternini: Cercyon (Paracercyon) Seidlitz, Cryptopleurum Mulsant and Pelosoma Mulsant (Coleoptera: Hydrophilidae) - Rodriguez, Georgina; Archangelsky, Miguel (Zootaxa, 2023)
The chaetotaxy of the head capsule and head appendages of all the larval instars of Cercyon (Paracercyon) analis and the first and third instars of Cryptopleurum minutum and Pelosoma sp. is described and illustrated for the first time. Morphometric characters derived from the head capsule and mouthparts are also included, together with detailed illustrations of all characters. The morphology and chaetotaxy of these larvae are compared to that of other Megasternini with described larvae. The larval morphology of Megasternini has proven to be very similar, however we provided a group of chaetotaxic characters useful to separate genera. Most of the differences were found in the sensilla of the head capsule, maxilla, and labium, both in size and arrangement, while the chaetotaxy of the antennae and mandibles was strongly conserved.